ChemInform Abstract: Aminocatalyzed Asymmetric Diels—Alder Reaction of 2, 4‐Dienals and Rhodanine/Hydantoin Derivatives. Issue 25 (3rd June 2013) - Zhu, Kailong; Huang, Huicai; Wu, Wenbin; Wei, Yuan; Ye, Jinxing
Abstract The title reaction proceeds via a trienamine mechanism and gives rise to the formation of spirocyclic compounds (III) and (V) in good yields and excellent stereoselectivities.